Research of the Influence of Structure Parameter on the Mechanics Property of Heavy Vehicle Drive Axle Housing - Ni Jinshang (Jixie chuandong)
To solve the problems of high design margin and high manufacturing cost of heavy vehicle drive axle housing,the parametric finite element model of heavy vehicle drive axle housing is established,through the drive axle housing of key structure parameters are set for the analysis variables,the influence of the structure parameter variables on the heavy vehicle drive axle housing mechanics characteristic is researched by using static,dynamic and fatigue life method,the reference for the design and choice parameters for the heavy vehicle drive axle housing is provided.The results show that the axle housing body length and the axle housing both sides of the baffle plate distance increase,the maximum stress value and deformation value of drive axle housing will increase;the axle housing body length and the axle housing around both sides of baffle plate distance of two parameters have less influences on natural frequency of driving axle housing,and the distance of the center line of the spring seat has great influences on natural frequency of drive axle housing.